Peramalan Jumlah Penduduk Kota Samarinda Dengan Menggunakan Metode Pemulusan Eksponensial Ganda dan Tripel Dari Brown - Reyham Nopriadi Gurianto; Ika Purnamasari; Desi Yuniarti (Program Studi Statistika FMIPA Universitas Mulawarman, 2016)
Forecasting is a process or method to predict an event that will occur in the future. Exponential smoothing is a method of moving average forecasting that conduct weighting decreases exponentially toward the value of the older observations. In this study discusses the Brown’s double exponential smoothing and Brown’s triple exponential smoothing method in predicting the population of the city of Samarinda in 2014, 2015 and 2016 are very necessary for the government to determine the population of the city of Samarinda. Double exponential smoothing method and triple from Brown is a method of extrapolation or by using a time series of past history in making the forecast for the future which used as a guide in decision-making processes. Results obtained using the method of Brown's double exponential smoothing using the parameter alpha of 0,52 was obtained that the forecast of total population in 2014 was 843.653 residents, in 2015 was 898.647 residents, and in 2016 was 944.716 residents with an average value deviation absolute (MAD) is 12.937 and the average -rata absolute percentage error (MAPE) is 2,4548. In the triple exponential smoothing method Brown’s using parameters alpha 0,4 obtained results forecast the total population in 2014 was 854.766 residents, in 2015 was 898.647 residents, and in 2016 was 944.716 residents with an average value deviation absolute (MAD) is 14.709 and the average percentage The absolute error (MAPE) is 2,7589.